Evaluation of copper bioaccumulation and translocation in Jatropha curcas grown in a contaminated soil - Ahmadpour, Parisa; Soleimani, Mohsen; Ahmadpour, Fatemeh; Abdu, Arifin (Taylor & Francis, 2014)
Contamination of soils with copper (Cu) has become a serious problem in the environment. Phytoremediation is an emerging green technology that uses green plants to remediate heavy metal contaminated areas. This study was conducted to evaluate the potential of Jatropha curcas for remediation of soils contaminated with Cu. Seedlings were planted in soils spiked with Cu in amount of 0, 50, 100, 200, 300, and 400 mg kg–1 (Cu0, Cu50,Cu100,Cu200,Cu300, and Cu400) for a period of five months. The maximum height and number of leaves were recorded in control (Cu0) whereas the highest basal stem diameter was found in seedlings exposed to Cu50. Copper concentrations among plant parts were in the following trend: roots > stems > leaves. The highest total Cu concentration (665 ± 1 mg kg−1) and total Cu removal (1.2 ± 0.2%) based on total plant dry biomass were found in Cu400 and Cu50 treatments, respectively. J. curcas exhibited high root concentration factor (RCF > 1) and low translocation factor (TF < 1). Although Cu accumulation by the plant didn't reach the criteria of Cu hyperaccumulators, this species showed a potential to be used in phytostabilization of mildly Cu contaminated areas. However, the plant cannot be used for phytoextraction of Cu-contaminated soils.